2013
DOI: 10.4103/2277-9175.108002
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization and PCR-Ribotypic profile of Pseudomonas aeruginosa isolated from cystic fibrosis patients in Iran

Abstract: Background:Pseudomonas aeruginosa, is the most common pathogen in patients with cystic fibrosis (CF) that shows various resistance to antibiotics, acquires mucoidity and multiple genotypes. This survey was performed to study phenotypic and genotypic variations among P. aeruginosa isolates in CF patients at Alzahra Hospital in Isfahan, Iran.Materials and Methods:The isolates of Pseudomonas aeruginosa from CF patients at Alzahra Hospital was identified by appropriate biochemical and microscopic tests, then perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
1
2
Order By: Relevance
“…In another study in Isfahan, based on antimicrobial susceptibility testing during 2003-2008 reported that the resistance rate of P. aeruginosa isolates from CF patients to amikacin and GEN, CIP, and CAZ were 9.5%, 14.2%, and 86%, respectively (14). Despite the geographic and time differences between the study by Forozsh et al (10) study and the recent study, there was little variation between the antibiotic resistance and susceptibility patterns.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In another study in Isfahan, based on antimicrobial susceptibility testing during 2003-2008 reported that the resistance rate of P. aeruginosa isolates from CF patients to amikacin and GEN, CIP, and CAZ were 9.5%, 14.2%, and 86%, respectively (14). Despite the geographic and time differences between the study by Forozsh et al (10) study and the recent study, there was little variation between the antibiotic resistance and susceptibility patterns.…”
Section: Discussioncontrasting
confidence: 48%
“…Despite the geographic and time differences between the study by Forozsh et al (10) study and the recent study, there was little variation between the antibiotic resistance and susceptibility patterns. In contrast, mentioned factors cause discrepancy among the results of the recent study and Fazeli et al study (14). Furthermore, it seems that hospital stay, age of the patients, and contact with CF cases might be risk factors for the acquisition of antibiotic resistant among strains of P. aeruginosa (10).…”
Section: Discussioncontrasting
confidence: 45%
“…As for the EOs, records include 57 plant species, representing 19 distinct taxonomic families such as Astereaceae [28], Lamiaceae [23], Myrtaceae [13], Apiaceae [9], Lauraceae [6], Melastomataceae [5], Convolvulaceae [2], Geraniaceae [ 2], Zingibereaceae [2], Phaeosphaeriaceae [1], Tamaricaceae [1],…”
Section: Descriptive Statisticsmentioning
confidence: 99%